2020
DOI: 10.1016/j.encep.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Prise en charge des comorbidités cardio-vasculaires chez les jeunes patients souffrant d’une psychose débutante : état des lieux et perspectives thérapeutiques

Abstract: Revue de la littérature Prise en charge des comorbidités cardio-vasculaires chez les jeunes patients souffrant d'une psychose débutante : état des lieux et perspectives thérapeutiquesManagement of cardiovascular co-morbidities in young patients with early onset psychosis: State of the art and therapeutic perspectives A. Frajerman a, ⁎, b

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Previous studies explained that the etiology of the EBP and DHL is a heterogeneous condition involving biological factors, genetics, depressive episodes, anxiety level, psychosocial aspect, cerebrovascular pathology, disorders of the endocrine system, presence of inflammatory processes, and nutritional status (46,47). Aligned with some previous studies (7,8,23,25,26,39,43,48), it is suggested the existence of a close relationship between hypertension disorders and mental health. The study shows that patients with cerebrovascular disease, especially in the anterior hemisphere, show mood lability.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous studies explained that the etiology of the EBP and DHL is a heterogeneous condition involving biological factors, genetics, depressive episodes, anxiety level, psychosocial aspect, cerebrovascular pathology, disorders of the endocrine system, presence of inflammatory processes, and nutritional status (46,47). Aligned with some previous studies (7,8,23,25,26,39,43,48), it is suggested the existence of a close relationship between hypertension disorders and mental health. The study shows that patients with cerebrovascular disease, especially in the anterior hemisphere, show mood lability.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, the study result shows that the classification of hypertension, especially the elevated blood pressure and hypertension level 1 on their SBP and DPB categories, are correlated to the Quality of Life. A previous study on caretaking depression and mental illnesses in the elderly shows it is more likely to be associated with anxiety (38,39). Hypertension and elevated blood pressure were also associated with anxiety through disruption of the autonomic nervous system, leading to higher variations in blood pressure and cardiovascular events (38,40,41).…”
Section: Discussionmentioning
confidence: 96%